PERAN KELUARGA DALAM MENINGKATKAN HUBUNGAN ORANG TUA DAN ANAK DI ERA DIGITAL - Ningsih, Wahyu; Nadia, Teti; Nurfattah Zahra, Ninda; Syifani, Fuzi (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2023)
The digital era is a term used in the emergence of digital, internet networks, or more specifically information technology. The digital era is marked by the existence of technology, where there is an increase in the speed and flow of knowledge in the economy and people's lives. Many changes that occur in society, be it from the economy, politics and almost all aspects of life can be affected by technological changes. One of them that is affected by technological advances is the role of the family in improving the relationship between parents and children, causing children to feel free and not controlled so that there are no limits in accessing or using gadgets. The research outlined in this journal aims to find out how the role of the family in improving the relationship between parents and children in the digital era like today. The research method used is qualitative using the descriptive method of analysis. The type of research used is library research, which is collecting data or scientific papers related to scientific ethics from a religious and scientific perspective that is literary. The role of parents in accompanying children in the digital era includes being a role model, supervising children's access and content, fostering open communication, and being actively involved in children's digital lives. Thus this approach, parents can help children develop a healthy and responsible understanding of technology, keep them safe in the digital world as well as build strong relationships within the family.